Recurrent bronchitis immunomodulation in children with vertebrobasilar arterial system syndrome - Ovcharenko, L. S.; Slutskaya Т. V.; Vertehel, A. A.; Andrienko, T. G.; Samokhin, I. V.; Kryazhev, A. V. (Modern medical technology, 2020)
Purpose of the study. To increase of recurrent bronchitis (RB) immunoprophylaxis effectiveness inchildrenaged 7 to 12 yearswiththevertebrobasilar arterial system syndrome (VBASS). Materials and methods. 60 children aged 7 to 12 years with RB and VBASS were examined. Two groups were formed (30 children each): 1) children with RB and VBASS receiving ω-3 polyunsaturated fatty acids (PUFA) at 300 mg per day during meals for 60 days; 2) children with RB and VBASS receiving multivitamins in a prophylactic daily dose during meals for 60 days. The state of immunity was assessed by data on phagocytosis, CD3, CD4, CD8, CD16, CD19, CD25, CD95; serum levels of IgA, IgG, IgM, tumor necrosis factor-α (TNF-α) and secretory sIgA in saliva. Results. When ω-3 PUFA is used, the frequency of registration of low indices of phagocytic index decreases (by 16,7%, p < 0,05), phagocytic number (by 28,4%, p < 0,05), index of phagocytosis completion (by 15,0%, p < 0,05), the spontaneous NST-test index (by 10,0%, p < 0,05), the CD16 content (by 10,0%, p < 0,05); the number of children decreases with an increase in CD3 (by 21,7%, p < 0,05), CD8 (by 15,0%, p < 0,05), CD19 (by 16,7%, p < 0,05), CD25 (by 31,6%, p < 0,05), CD95 (by 18,4%, p < 0,05), serum IgG (by 11,7%, p < 0,05), IgM (by 31,7%, p < 0,05), TNF-α (by 30,0%, p < 0,05) and decreased IgA level (by 15,0%, p<0,05), saliva sIgA (by 31,6%, p < 0,05). Conclusions. The use of ω-3 PUFA is an effective remedy for RB immunoprophylaxis in children with (на 11,7%, р < 0,05), IgМ (на 31,7%, р < 0,05), ФНО-α (на 30,0%, р < 0,05) и сниженного уровня IgА (на 15,0%, р < 0,05), sIgA слюны (на 31,6%, р < 0,05). VBASS, which is associated with the universal regulatory mechanism of immunotropic influence – protective and anti-inflammatory.